Developing Muslim Communities in The Philippines Through Transformational Leadership: An Islamic Perspective - RACHMAN, SAPIA ABDUL; SUMRAHADI, ABDULLAH; MAKOL, BADRIYA P (Jurnal Studi Pemerintahan, 2012)
This research concludes that development of Muslim communities in the Philippinesprimarily relies on local initiatives and people’s assertive character to institute behavioralreform. It entails a transformation process involving all sectors of the society in such a waythat true and committed Muslim leaders will emerge to provide direction and at the same timeorchestrate the development of the communities.It is therefore argued that transformationalleadership is the most appropriate model that could improve the living conditions of Muslimsin the Philippines Firstly, this study provides the empirical evidence that leaders and followersbelieve that it is through Islamic leadership that their communities can be developed. Secondly, thehistory of the leadership of Prophet Mohammad and his four caliphs proved that Islamic leadership isindeed transformational leadership one, hence, they deserve to be emulated by Muslims.